2020
DOI: 10.12688/hrbopenres.13074.3
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of young carers’ experiences of school and their perceptions regarding their future career - a scoping review protocol

Abstract: Background: Young carers are young people who care for a relative or a friend with an illness, disability, frailty, a mental health issue or addiction. Across the world, it is challenging to calculate the exact numbers due to the invisible nature of their role that can exist due to stigmatisation and fear of authoritative intrusion. As young carers reach 16 years and over, future career prospects become more significant. Young carers are more likely than their peers not to be in education, employment, or train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This is further supported by the University of Oxford ( 2015), who found that 54% of surveyed carers said they felt they would have achieved higher, had they not had a responsibility of care whilst studying. Whilst this lower-than-average attainment may be accredited to the substantial responsibilities held by young carers (Wong, 2017), this may highlight a need for further, more established, frameworks to be placed in schools to recognise the specific needs of those in a position of care (Moloney et al, 2020), with the aim to close the attainment gap, which may improve employment rates within young carers.…”
Section: Caring Negatively Impacts Education and Employment Opportuni...mentioning
confidence: 99%
See 1 more Smart Citation
“…This is further supported by the University of Oxford ( 2015), who found that 54% of surveyed carers said they felt they would have achieved higher, had they not had a responsibility of care whilst studying. Whilst this lower-than-average attainment may be accredited to the substantial responsibilities held by young carers (Wong, 2017), this may highlight a need for further, more established, frameworks to be placed in schools to recognise the specific needs of those in a position of care (Moloney et al, 2020), with the aim to close the attainment gap, which may improve employment rates within young carers.…”
Section: Caring Negatively Impacts Education and Employment Opportuni...mentioning
confidence: 99%
“…In addition, young carers will find themselves restricted by distance and flexibility of the role, with many arguing that they must remain within a reasonable distance of the person requiring care, thus limiting employment options (Skovdal et al, 2009). The same could apply for further and higher education, as not all carers will have access to a local university (Moloney et al, 2020) and travel restriction not only affects long term work and education prospects, it could also negatively impact upon personal development and career progression (Crawford et al, 2016).…”
Section: Caring Negatively Impacts Education and Employment Opportuni...mentioning
confidence: 99%
“…Young carers are not necessarily in situations of poverty and deprivation, but the evidence indicates that many of them are in homes with very limited resource (Vizard et al, 2019). Research studies from the UK and Australia indicate that young carers have complex and busy lives and may struggle to attend to their school studies which can compromise opportunities in future employment and Further and Higher Education (Moloney et al, 2020;Moore & Barry, 2014). Further challenges for young carers arose during restrictions and lockdowns as the support for registered carers from social services was often limited or suspended as social service staff reduced physical contact time.…”
Section: Young Carersmentioning
confidence: 99%